Batam City’s Competitive Position as an Investment Destination in the Southeast Asia Region in 2021-2022 - Annisa Aqila Azza; Agustinus Moruk Taek (Journal of World Trade Studies, 2024)
The increase in investment in Batam during the 2021–2022 period has reinforced Indonesia's position as a leading investment destination in Southeast Asia. As a Special Economic Zone and Free Trade Area, Batam offers a range of investment incentives, continuously developing infrastructure, and investment-friendly economic policies. This article aims to identify Batam’s strategic position as an investment destination within the Southeast Asian region. The study employs a descriptive qualitative method, utilizing a literature review approach and secondary data analysis obtained from the Badan Pengusahaan Batam (BP Batam). The findings indicate that Batam experienced a significant increase in realized investment despite the global challenges posed by the COVID-19 pandemic. Key factors driving this growth include the city's expanding infrastructure, pro-investment government policies, and high economic competitiveness, all of which have contributed to enhancing Batam’s investment appeal and strengthening its position in Southeast Asia. This success presents a model that may be replicated in other regions by reinforcing regulatory reforms, infrastructure development, and digital service delivery, thereby fostering a more inclusive and sustainable investment climate.